A arte de letrar o Kiriri: protagonismo de línguas indígenas no Português do Semiárido Baiano - Santana, Rejane Cristine Carneiro (2025)
The Kipeá and Dzubukuá languages, belonging to the Kiriri family within the Macro-Jê linguistic trunk, played a central role in the catechization of the Aldeias do Sertão (Hinterland Villages) during the 17th and 18th centuries. They served as the ‘official’ language in the ‘art of indoctrination’ and triggered a shift in the methodology of this catechetical process, which had previously been carried out in Língua Geral in colonial Brazil. These languages were also pioneers in producing written records of non-Tupi languages in the 18th and 19th centuries, Arte de Grammatica da Lingua Brazilica da Nação Kiriri (1699) e o Catecismo Kiriri (1698) do padre jesuíta italiano Luiz Vincencio Mamiani; Catecismo da Língua Kariri do capuchinho francês Bernardo de Nantes (1706).Thus, from the perspective of Historical Linguistics and the social history of language, this research aimed to study the impact of the Kiriri languages as a catechetical tool in the villages of Pambu, Canabrava, Natuba, and Saco dos Morcegos, as well as their linguistic marks on the formation of Brazilian Portuguese (hereafter BP) up to the present day.The theoretical framework of this study is grounded in the works of: i) Almeida (1997); ii) Mattos e Silva (2004) and who offer valuable discussions on socio-historical linguistic research, particularly through the analysis of early written records from a bibliographic/documental perspective, attentive to all the historical agents involved and to the reinterpretation of facts; iii) D’Angelis (2007), iv) Edelweiss (1958), v) Ivo (2017), vi) Rodrigues (2012), who present descriptive studies of Brazilian Indigenous languages; xi) Seabra (2006), xii) Biderman (2001), xii) Isquerdo (2009), who focus on the lexicon and its external representations through the act of naming, aiming to understand past customs and practices. From these investigations, 36 lexical findings were identified and classified as follows: i) seventeen toponyms in Kiriri languages recorded on historical maps of the states of Bahia, Sergipe, and Pernambuco; ii) fifteen living lexical items documented in the works of Father Vicencio Mamiani (1699) and Friar Bernardo de Nantes (1709), which are still in use in the semi-arid region of Bahia. This study contributes new data to the Social History of Language and to research on Indigenous languages of the Macro-Jê trunk, as well as to the historiography of Indigenous peoples in Bahia.